Expression of Low Molecular Weight Heat-Shock Proteins under Field Conditions. - Hernandez, L. D. (1993)
Heat-shock proteins (HSPs) are known to be expressed in plants experiencing high-temperature stress. We have examined the expression of class I cytoplasmic low molecular weight (LMW) HSPs and find that these HSPs also frequently accumulate in seeds, seed pods, and flowers during a normal growing season. We first examined the expression of class I cytoplasmic LMW HSPs by western blot analysis in a range of seed samples from both commercially grown and wild legumes. LMW HSPs were present in all seed samples, indicating that these HSPs are regularly expressed in these tissues. To examine more specifically conditions under which LMW HSPs were produced during an average growing season, additional studies of Medicago sativa were carried out during the fall season in Tucson, AZ. Plants were irrigated to avoid conditions of water stress, and canopy temperature was monitored throughout the study period. LMW HSP expression in leaves, flowers, and developing seed pods was analyzed by western blotting. Results show that in the field HSPs are frequently produced in flowers and seed pods, even in plants that show no HSP expression in leaves. Parallel greenhouse studies indicate that HSP expression in seeds is in part developmentally regulated. In total our data suggest a more widespread occurrence of HSPs in optimal growth environments and emphasize their potential role during reproduction.